Ultrafast spectroscopy : quantum information and wavepackets /: quantum information and wavepackets. (2014) - Yuen-Zhou, Joel; Krich, Jacob J; Kassal, Ivan; Johnson, Allan S; Aspuru-Guzik, Alán
No abstract available